European Union Delegations in EU Foreign Policy A Diplomatic Service of Different Speeds - Austermann, Frauke; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This first comprehensive study of the EU's diplomatic representation in the world, the EEAS, this book seeks to understand why it has failed to formulate a centralised policy towards external states. It also analyses why the EEAS has more success in centralising diplomatic structures in developing countries than with some economic partners.
Keywords: Science; Science; Science, general